Asymmetric and symmetric dimethylarginine in high altitude pulmonary hypertension (HAPH) and high altitude pulmonary edema (HAPE) - Hannemann, Juliane; Freytag, Julius; Schiefer, Lisa Maria; Macholz, Franziska; Sareban, Mahdi; Schmidt-Hutten, Lena; Stang, Heike; Schwedhelm, Edzard; Swenson, Erik R.; Böger, Rainer; Berger, Marc Moritz (Frontiers in Physiology, 2023)
High altitude exposure may lead to high altitude pulmonary hypertension (HAPH) and high altitude pulmonary edema (HAPE). The pathophysiologic processes of both entities have been linked to decreased nitric oxide (NO) availability. We studied the effect of acute high altitude exposure on the plasma concentrations of asymmetric (ADMA) and symmetric dimethylarginine (SDMA), L-arginine, L-ornithine, and L-citrulline in two independent studies. We further investigated whether these biomarkers involved in NO metabolism were related to HAPH and HAPE, respectively. Fifty (study A) and thirteen (study B) non-acclimatized lowlanders were exposed to 4,559 m for 44 h and 67 h, respectively. In contrast to study A, the participants in study B were characterized by a history of at least one episode of HAPE. Arterial blood gases and biomarker concentrations in venous plasma were assessed at low altitude (baseline) and repeatedly at high altitude. HAPE was diagnosed by chest radiography, and HAPH by measuring right ventricular to atrial pressure gradient (RVPG) with transthoracic echocardiography. AMS was evaluated with the Lake Louise Score (LLS) and the AMS-C score. In both studies SDMA concentration significantly increased at high altitude. ADMA baseline concentrations were higher in individuals with HAPE susceptibility (study B) compared to those without (study A). However, upon high altitude exposure ADMA only increased in individuals without HAPE susceptibility, while there was no further increase in those with HAPE susceptibility. We observed an acute and transient decrease of L-ornithine and a more delayed but prolonged reduction of L-citrulline during high altitude exposure. In both studies SDMA positively correlated and Lornithine negatively correlated with RVPG. ADMA was significantly associated with the occurrence of HAPE (study B). ADMA and SDMA were inversely correlated with alveolar PO 2 , while L-ornithine was inversely correlated with blood oxygenation and haemoglobin levels, respectively. In nonacclimatized individuals ADMA and SDMA, two biomarkers decreasing endothelial NO production, increased after acute exposure to 4,559 m. The observed biomarker changes suggest that both NO synthesis and arginase pathways are involved in the pathophysiology of HAPH and HAPE.